Sustainable Development Aspects in Cross-Border Cooperation Programmes: The Case of Croatia and Montenegro - Marijana Sumpor; Marga Kuzmić (European Regional Science Association (ERSA), 2011)
The cross-border area between Croatia and Montenegro has similar development preconditions: large potential for tourism development and rich natural and cultural heritage. Both have experience in EU funded cross-border cooperation (CBC) programmes. The importance of the sustainable development aspect and is formally included into various national strategic documents, but implementation of such vague strategic documents is often problematic and sustainability aspects need to be examined on programme and project level. The current Integrated Pre-accession Assistance (IPA) Cross-border Cooperation Programme Croatia-Montenegro 2007-2013 is the basis for our research and sustainability evaluation. As recognised in the Cross-border Cooperation (CBC) Programme, one of the main challenges of the cross-border area besides the impact of globalization on the regional economy and developing competitive economy based on knowledge etc., are also environmental challenges. The Programme's strategic orientation to sustainable development encompasses economic development, human resources development, social justice and environmental protection. The overall objective focuses on the development of the cross-border region through cooperation and networks following the guidelines and regulations provided by the European Commission (EC) through the IPA Implementing Regulation. Specific objectives focus on development of SMEs, tourism, trade, environment, culture and sport. The long-term opportunities for the programming area are: competitive regional economies based on high quality service sector in tourism; efficient protection of the environment; natural and cultural heritage; and sustainable use of nature resources; as well as high quality public and social services necessary for community development. At project level, environmental issues were only to a very limited degree included and addressed in the application package through evaluation of financial, institutional, policy level and environmental sustainability aspects. Since the CBC Programme is implemented through projects, our questions are the following: What is the structural impact of the proposed actions and do they lead to improved legislation, codes of conduct, and methods? Is there an environmental impact? To which extent is guidance on sustainability issues provided and what is needed for improved implementation? How are participatory approaches during project planning and implementation used?
Keywords: 330